Research trends of scientific literacy in Indonesia: Where are we? - Fatchiyatun Ni'mah (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2019)
Scientific literacy has become a trend of research in various international research journals. These research trends also influence research trends in Indonesia. The purpose of this study is to analyze research related to scientific literacy in Indonesia based on articles published in various national journals. The analysis was conducted in term of methodological approach used and the subjects studied. The analysis was conducted on 138 articles published in various national journals, whether they have been indexed by SCOPUS, DOAJ or other journal indexing agencies. The findings indicate that the application of learning to increase student’s scientific literacy is new research trend in Indonesia and commonly conducted in science major (IPA) with Junior High School students as samples. This study provides an overview of perspectives in scientific literacy research in Indonesia.